Pengaruh Pengangguran dan Kemiskinan Terhadap Pertumbuhan Ekonomi di Provinsi Gorontalo - Mohamad Arif Novriansyah (Gorontalo Development Review, 2018)
The province of Gorontalo as a resultant area of the North Sulawesi Province is certainly faced with unemployment and poverty problems, which is a common development problem faced by every region. the population condition of the area shows that the population in each regency in Gorontalo Province varies from one to another. From the condition of the population then needs to be analyzed about the effect of unemployment and poverty on economic growth in Gorontalo Province.The purpose of this study is to determine the effect of unemployment and poverty on economic growth in Gorontalo Province. The results show that unemployment and poverty affect economic growth in Gorontalo Province. This is also in accordance with the results of calculations using a simple regression, where the level of significance of the whole one-sided correlation coefficient as measured by probability yields a figure of 0.019. Since the probability is less than 0.05, the correlation between the variables of unemployment and poverty (Variables X1 and X2) and economic growth (Variable Y) is significant.